Molecular Mechanism of Deguelin in Anti-tumor Effect - Wen, Lu; Chen, Yan (Current Pharmaceutical Analysis, 2012)
Deguelin is the major active ingredient and principal component in cube resin, derived from Lonchocarpus utilis and used as a botanical insecticide and pesticide in Africa, South America and China. A growing body of evidence indicates that deguelin has a very strong anti-tumor effect on malignant cells without compromising normal cells. As a complex natural extract, deguelin interacts with various molecular targets to exert its anti-tumor properties at nanomolar levels. This current review delineates the molecular mechanism of the anti-tumor activities of deguelin in malignancies. Our research shows that the multiple and extensive biological effects of deguelin are mediated via interactions with target points involved in cell proliferation pathways (cyclin D1, pRb), cell apoptosis pathways (NF-κB, IκBα, Bcl-2, Bcl-xl, survivin), the nucleophosmin and nucleoporins pathways (Nup88, Nup98, Nup214), as well as through the regulation of steroid receptor co-activator SRC-3 and DNA Topoisomerase. In addition, deguelin holds a promising efficacy for reversing drug resistance.
Keywords: NF-κB